2012
DOI: 10.1007/s00414-012-0694-6
|View full text |Cite
|
Sign up to set email alerts
|

Forensic and phylogeographic characterisation of mtDNA lineages from Somalia

Abstract: The African mitochondrial (mt) phylogeny is coarsely resolved but the majority of population data generated so far is limited to the analysis of the first hypervariable segment (HVS-1) of the control region (CR). Therefore, this study aimed on the investigation of the entire CR of 190 unrelated Somali individuals to enrich the severely underrepresented African mtDNA pool. The majority (60.5 %) of the haplotypes were of sub-Saharan origin with L0a1d, L2a1h and L3f being the most frequently observed haplogroups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…The majority of the mtDNA haplotypes (92.24%) are included in macrohaplogroup L. Haplogroup L2a1a is the most frequent haplogroup found in the present study (12.621%). Phylogram representing F st distances between the Cabo Verde population of Lisbon and selected populations from the literature (Fendt et al 2012a, b;Mikkelsen et al 2012) are shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the mtDNA haplotypes (92.24%) are included in macrohaplogroup L. Haplogroup L2a1a is the most frequent haplogroup found in the present study (12.621%). Phylogram representing F st distances between the Cabo Verde population of Lisbon and selected populations from the literature (Fendt et al 2012a, b;Mikkelsen et al 2012) are shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…These populations also share the most common haplogroups. Somalia, a country in the east African coast, has as most common haplogroups L0a1d, L2a1h and L3f, characteristic of east and southeast Africa, and M1 and N1, characteristic of northeast Africa and Middle East (Mikkelsen et al 2012). Analysis of the entire mtDNA control region for the first time in Cabo Verde native individuals increased the discriminatory power between samples and overall efficiency in the determination of haplogroups.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is also true for Asian-Indonesian haplogroups M7c3c, M32, E1a1a or F3b1. A comparison of the mtDNA haplogroup distribution in Madagascar with Asian or African populations [23][24][25][26][27][28] underlined the special position of the Malagasy (Supplementary Figure S3) who cluster with none of the other populations.…”
Section: Maternal Lineagesmentioning
confidence: 99%
“…The high frequency of haplogroups L shown in African populations, as well as the high level of heterogeneity of the mitochondrial DNA sequences in this continent have been reported several times, being higher than in other geographical regions [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Studies regarding mtDNA total control region of African populations have been performed [31][32][33]37]. However, sequences of mtDNA total control region of Angolan individuals are not published.…”
Section: Introductionmentioning
confidence: 99%